Noise baseline data for Ninoy Aquino Parks and Wildlife Nature Center a protected area - Mendoza, Victorino C. (1997)
Ninoy Aquino Parks and Wildlife Nature Center (NAPWNC) is one of the Protected Areas (PA) considered as an initial component under the existing Republic Act 7586 known as the National Integrated Protected Areas System (NIPAS) Act of 1992. Currently, NAPWNC is considered an area of national significance which is characterized by harmonious interaction of man and nature while providing opportunities for public enjoyment through recreation and tourism. In order to continue enhancing the quality of service to the visiting public, one of the intentions of this study is to help the administration of NAPWNC in the management of the said park through proper sectoring and zoning for a better and functional use as far as environmental noise and related cotrol measures are concerned. Under the existing Department of Environment and Natural Resources (DENR) Environmental Quality Standard for Noise in General Areas, NAPWNC - PA is not yet specifically classified.
The setting to fast and instantaneous methods of the sound level meter was used in monitoring design schedule of sound intensity level within the NAPWNC area. The existing operational procedure for noise measurement of the DENR stated under the Official Gazette, Article 1 of Section 79, a-c [NPCC (12)] has been applied in gathering data to attain the quality of monitoring objectives. This method is expected to give reliable results for setting up noise baseline data. The data gathered from the ambient sound level condition at the different established stations within NAPWNC can be used as baseline data in deriving a single and comprehensive regulation for the entire protected area throughout the Philippines with the same typical protected area (PA) set up. This baseline data can also be an important material in the preparation of Environmental Impact Assessment (EIA) for any proposed project within NAPWNC compound and its adjacent areas. Further to setting up the noise baseline data (NBD), this study details out procedures in data gathering as well as establishing noise trends and intensity levels within a certain study area. This will be an invaluable tool to others who are intending to pursue further studies in this field of endeavor.
Thesis (M.S. Environmental Engineering)--University of the Philippines Diliman.
Keywords: Noise control; Noise -- Physiological effect